DETERMINATION OF THE CLASS B FIRE EXTINGUISHING PARAMETERS USING SPRAYED WATER - Abramov, Yu.; Kolomiiets, V.; Sobyna, V. (Municipal economy of cities. Series: «Economy science», 2024)
Sprayed water is a versatile tool for localising and extinguishing fires of various types. When water evaporates, its volume increases by 1700 times, resulting in the dilution of combustible components with non-combustible water vapour. The study aims to determine the parameters of extinguishing class B fires using sprayed water by obtaining analytical dependencies for these parameters. The paper derives an expression for the extinguishing temperature of class B fires when extinguished with sprayed water, using Semenov’s conditions. The process of liquid combustion is considered as diffusion. The study shows that the extinguishing temperature of this type of fire is a function of the activation energy of the burning liquid and the initial temperature (at the time of sprayed water supply) of the flame. A parameter of this function is the universal gas constant. The authors constructed a graph showing the area of change in the fire extinguishing temperature. The difference between the initial flame temperature and the fire extinguishing temperature belongs to the range of (80÷120) °C. Using the transition function of class B fire, the study derives an expression for its extinguishing time, which depends on the initial flame temperature, activation energy, and the multiplicative component in the form of a fire time constant. For the relative extinguishing time, the authors constructed the area of change in this parameter depending on the activation energy and the initial temperature. It shows that the value of the extinguishing time of such a fire is (0.28÷0.32) of the value of the constant fire time. The paper presents an expression for the minimum value of the intensity of the sprayed water supply, which ensures extinguishing a class B fire. This intensity of the supply of sprayed water, reduced to the value of the fire transmission coefficient, is determined by the initial temperature of the flame and the activation energy of the liquid that burns. The authors constructed the area of change of this fire extinguishing parameter. It shows that the minimum value of the intensity of the supply of sprayed water belongs to the range (3.8÷7.8) per unit of the fire transmission coefficient.